ANALISIS HUKUM TERHADAP KESEIMBANGAN KEDUDUKAN PARA PIHAK DALAM PERJANJIAN PENGADAAN BARANG/JASA PEMERINTAH (STUDI PERJANJIAN NOMOR: 027/256/SES PENGADAAN KENDARAAN RODA EMPAT ANTARA PEJABAT PEMBUAT KOMITMEN BADAN PENELITIAN DAN PENGEMBANGAN KEMENTERIAN D - THOMMY HENKARY SIHITE (PREMISE LAW JURNAL, 2016)
A contract on procuring government’s goods/services is a contract between the government and a contractor in order to fulfill the need for government’s goods and services which source of fund comes from the Regional Generated Revenues. The contract is made in the form of standard contract; that is, a contract which has been prepared by the user. The thesis explained the judicial correlation between the user of goods, the Secretary of Research and Development Board as the official empowered to make the commitment and, PT. Suzuki Indomobile Sales as the goods provider. In the contract, there is no sanction imposed upon the user if it delays the payment while the sanction will be imposed on the provider if it has bad performance, and if the provider feels that it is harmed, it cannot cancel the contract, while the user has the right to cancel it. The conclusions of the research showed that there were some imbalances in the contract: the provider’s obligation was clearly described while the user’s was not, only the user had the right to cancel the contract, black list sanction would be imposed on the provider while there was no sanction on the user, and legal remedy could be done through litigation and non-litigation. Keywords: Balance, Contract, Procurement of Government’s Goods and Services